Membina Keahlian Pertambangan: Pembelajaran Aktif dan Pelatihan Laboratorium di PT Bukit Asam Tanjung Enim untuk Mahasiswa Universitas Sriwijaya - Rosihan Pebrianto; Marwan Asof; Diana Purbasari (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Since the outbreak of the COVID-19 pandemic in early 2020, many processes in teaching and learning have experienced significant disruption, hindering implementation as originally planned. The impact of this is that some learning materials are not provided adequately, resulting in reduced student skills. Therefore, measures of field observations and practical participation have been designed and implemented with the aim of encouraging students to improve their skills. In this initiative, the observation method is used in conjunction with practical training sessions. The holistic approach allows students to learn holistically through real-life observations and real-world applications. The results of this activity are carefully evaluated, focusing on comparing the students' initial ability before participating in the program and their achievements after participating in this series of activities. Analysis of these assessments showed that mastery of the theoretical material has increased significantly, with an average increase of 42%. In addition, in terms of actual application there is a more pronounced increase, with an average actual capacity increase of 97.625%. These results clearly reflect the effectiveness of field observations and practical practices in enhancing students' skills, both in theory and in practical application.